A multi-channel peripheral nerve stimulator with integrate-and-fire encoding. (3rd April 2021) - Kundu, Aritra; Fahmy, Ahmed; Madler, Ryan; Otto, Kevin; Patrick, Erin; Principe, Jose; Maghari, Nima; Bashirullah, Rizwan
Abstract: Activation of peripheral nervous system (PNS) fibres to produce variable tactile and proprioceptive sensations in advanced bidirectional prosthetic limbs relies on neural stimulators with high spatial selectivity, dynamic range and resolution. A multi-channel application-specific integrated circuit (ASIC) is developed for PNS fibre activation using a wide dynamic range (10 nA–5 mA), high-resolution (30 nA step, 100 ns pulse accuracy) current stimulator, dissipating 0.73–2.75 mW at 3 V. The ASIC also enables encoding of external pressure signals via an integrate-and-fire methodology. Electrophysiological data of compound nerve action potentials were recorded for a range of stimulus amplitudes and pulse widths. This data was used to benchmark the performance of the ASIC with a known neural stimulator.